Reimagining history education through the arts: An exploratory study on active and experiential learning - Siti Utami Dewi Ningrum; Nisa A'rafiyah Tri Wulandari; Mutia Kamalia Mukhtar; Muhammad Nirwan Sambudi; Siti Trisna Dewi (Jurnal Sinar Edukasi, 2026)
History education is often text-based and tends to fall short in connecting students with emotional and reflective experiences of the past. This study aims to explore various forms of art, such as novels, films, paintings, and songs, as media for history education that can foster active engagement and experiential learning among students. Through an interdisciplinary approach that maps the potential and functions of artistic works within the context of history education, this study highlights how art can serve as a powerful narrative medium to enrich critical understanding, empathy, and personal reflection on historical events in Indonesia. The research findings indicate that works of art have the capacity to serve as humanistic historical material, challenge dominant narratives, and foster a deeper connection between students and the past. This exploratory mapping provides a conceptual foundation for the development of innovative, student-centered history learning strategies that are more emotionally engaging, culturally relevant, and intellectually stimulating.